(untitled) (Economic studies journal, 2018)
The aim of this study was to identify the impact of organizational culture on the organizational conflict in the private insurance companies in Tripoli. The researchers relied on the descriptive approach using a questionnaire as a tool for collecting the study data. This questionnairs were distributed to about (191) respondents. The data of study and the validity of the main hypothesis and the sub-hypotheses derived from it were analyzed through the application of descriptive and explanatory analysis tools using the Statistical Package for Social Sciences (SPSS). The results of this study showed that the development of organizational culture (teamwork, innovation and innovation) is high, while the adapting to the environment is moderate. In addition, a negative trend was indicated and it referes to is a high level of self-conflict. The study also showed that there is a significant effect on the organizational conflict of the dimensions of the organizational culture (collective action, innovation and innovation), while the effect of the dimension (adaptation to the environment) has a significant impact on organizational conflict. The study recommended that the senior management should take care of the companies concerned with the environmental conditions and conducting training courses for the employees to acquire the ability to adapt to the changes and environmental conditions, as well as to ease the negative conflict to the minimum level